2018
DOI: 10.1093/gerona/gly264
|View full text |Cite
|
Sign up to set email alerts
|

Multiple Sensory Impairment Is Associated With Increased Risk of Dementia Among Black and White Older Adults

Abstract: Background: Few studies have examined impairment in multiple senses (multisensory impairment) and risk of dementia in comparison to having a single or no sensory impairment. Methods: We studied 1,810 black and white nondemented participants from Health, Aging, and Body Composition (Health ABC) Study aged 70-79 years at enrollment. Sensory impairment was determined at our study baseline (Year 3-5 of Health ABC) using established cut points for vision (Bailey-Lovie visual acuity and Pelli-Robson contrast sensiti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
147
3

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 103 publications
(156 citation statements)
references
References 37 publications
6
147
3
Order By: Relevance
“…The link between hearing impairment and cognitive impairment may be due to a common underlying cause such as vascular disease (3,34) or neurodegenerative diseases such as Alzheimer's disease. However, control for prevalent cardiovascular disease, cardiovascular risk factors, and genetic risk for Alzheimer's disease did not change the observed associations.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…The link between hearing impairment and cognitive impairment may be due to a common underlying cause such as vascular disease (3,34) or neurodegenerative diseases such as Alzheimer's disease. However, control for prevalent cardiovascular disease, cardiovascular risk factors, and genetic risk for Alzheimer's disease did not change the observed associations.…”
Section: Discussionmentioning
confidence: 99%
“…With the aging of the population and high costs associated with caring for cognitively impaired older adults, identification of risk factors for cognitive decline in aging is becoming increasingly important. Hearing impairment, which affects 60%-68% of U.S. adults older than 70 years (1), is recognized as a risk factor for age-related cognitive impairment, disability, and dementia (2)(3)(4)(5). A recent systematic review and meta-analysis indicated that age-related hearing loss was associated with twofold or greater pooled odds of cognitive impairment and dementia in cross-sectional studies (6).…”
mentioning
confidence: 99%
“…[4][5][6][7][8] The administration of cognitive screening tools, including the MoCA, has become a notable area of research as associations have been found between sensory impairments (eg, loss of vision and hearing loss [HL]) and cognitive deficits. [9][10][11][12] For example, HL has been associated with impairments across several cognitive domains (eg, immediate and delayed recall, processing speed, and semantic memory) and dementia. 12 Though these relationships range from weak to moderate, 12,13 the contributions of HL are similar in magnitude to other modifiable risk factors of dementia (eg, obesity, diabetes, and hypertension).…”
Section: And the Montreal Cognitive Assessmentmentioning
confidence: 99%
“…The administration of cognitive screening tools, including the MoCA, has become a notable area of research as associations have been found between sensory impairments (eg, loss of vision and hearing loss [HL]) and cognitive deficits . For example, HL has been associated with impairments across several cognitive domains (eg, immediate and delayed recall, processing speed, and semantic memory) and dementia .…”
Section: Introductionmentioning
confidence: 99%
“…Hearing loss and vision loss have been associated with dementia in HIC (38)(39)(40)(41)(42), but evidence for these associations in Latin America or other LMIC is lacking. The current results suggest that eye problems, but not hearing problems, are associated with an increased risk of dementia in Cuban older adults, but only in the older age group.…”
Section: Health Factorsmentioning
confidence: 99%